Optimal Degrees of Tranaparency in Monetary Policymaking. - Henrik Jensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2001)
According to most academics and policymakers, transparency in monetary policymaking is desirable. I examine this proposition in a small theoretical model emphasizing forward-looking private sector behavior. Transparency makes it easier for price setters to infer the central bank's future policy intentions, thereby making current inflation more responsive to policy actions. This induces the central bank to pay more attention to inflation rather than output gap stabilization. Then, transparency may be disadvantageous. It may actually be a policy-distorting straitjacket if the central bank enjoys low-inflation credibility, and there is need for active monetary stabilization policy.
Keywords: 330